Decreased layer specific longitudinal strain in myocardial segments supplied by stenosed LAD coronary artery: analysis for baseline, peak and recovery phase of stress echocardiography. (25th November 2020) - Kowalczyk, E; Kasprzak, J.D; Hamala, P; Nowak, B; Nowakowski, R; Trzos, E; Lipiec, P; Wierzbowska-Drabik, K
Abstract: Background: Despite wide utility of global longitudinal strain in the assessment of left ventricular function up to now little is known about layer specific quantification of myocardial function during stress tests and its potential for ischemia detection. Purpose: To investigate diagnostic utility of layer specific LS during stress echocardiography using marker segments in patients with established Left Anterior Descending (LAD) coronary artery status. Methods: We retrospectively analyzed 63 patients (mean age 62.5±9.9 years, 62% males) with suspected coronary artery disease, who had performed dobutamine stress echocardiography (DSE). Layer specific speckle tracking LS analyses were performed during rest, maximal stress and recovery. As a marker for LAD (segment most probably supplied by this artery) we used mid-anterior left ventricle segments. LAD status were established with coronary angiography or angioCT and consider as significant if ≥70% stenosis was present. Results: In our study group 14 patients had significantly stenosed LAD (group 1) and 24 had normal coronaries (group 2). We detected significantly lowered absolute values of strain in endocardial and mid-myocardial layers of segments supplied by stenosed LAD at rest for endocardium −8.6% (group 1) vs −13.4% (group 2); p=0.045; and mid-myocardium −7.3% (group 1) vs −11.2% (group 2); p=0.044. Moreover, we observed similar trend at recovery, however without reaching statistical significance. Conclusions: Longitudinal strain analysis focused on segments supplied by assessed coronary artery my provide quantitative data confirming ischemia in the settings of rest and stress echocardiography. Our pilot study suggest that for inotropic agents like dobutamine the potential ischemic dysfunction may be however masked at peak stage of the test. Funding Acknowledgement: Type of funding source: None